Maarifa Knowledge Centres - Harvey, Blane; Ensor, Jonathan; Carlile, Liz; Garside, Ben; Patterson, Zachary; Naess, Lars Otto (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2012)
Initiated in 2007, the Maarifa Centres (Maarifa is the Swahili word for knowledge) are a project that aims through multimedia tools, to facilitate the exchange of ideas, experiences, and knowledge among communities to enhance learning for improved socio-economic empowerment. The project involves the establishment of community knowledge centres (CKC) in the rural areas of Kenya, Tanzania, and Uganda which, in partnership with other agencies, seek to bring information and communication technologies (ICTs) to rural communities to enable the documentation and sharing of local knowledge - in particular, knowledge relating to farming and natural resource management.